Experiences of participating in a preoperative comprehensive geriatric assessment and care intervention among frail older adults before colorectal cancer resection surgery - Kristina Åhlund; Lena G. Larsson; Niklas Ekerstad; Maria Normann; Mattias Prytz; Anette Johnsson (BMC Geriatrics)
Abstract Background Comprehensive geriatric assessment (CGA) and care has shown benefits for frail older adults across various care settings. However, its integration into routine care within a surgical context remains limited. An ongoing randomised controlled multicentre study will evaluate the effects of a period of preoperative optimisation (up to eight weeks), involving interprofessional CGA and care, in addition to routine care before colorectal cancer resection surgery. If this approach proves favourable, it could potentially be incorporated into routine surgical care. To facilitate implementation, it is crucial to explore and understand participants’ perceptions of taking part in a preoperative CGA and care intervention. Aim To describe how frail older adults with colorectal cancer experience participation in a preoperative CGA and care intervention. Methods This qualitative, descriptive study was part of a randomised controlled multi-centre study. In total, 20 semi-structured interviews were conducted with frail older adults undergoing a CGA and care intervention before colorectal cancer surgery. The data were analysed using inductive qualitative content analysis. Results Frail older adults with colorectal cancer experienced participation in preoperative CGA and care as an integral part of an intervention. They adopted an opportunity mindset when deciding to participate. Throughout the intervention, they observed the team working collaboratively and actively involving them in the optimisation process, enhancing their readiness for surgery by the end of the period. Conclusions The findings indicated that frail older adults with colorectal cancer viewed the preoperative CGA and care intervention as a meaningful opportunity for improvement and a chance to extend life. Their active involvement and the collaborative efforts of the care team during the intervention were crucial in enhancing their understanding, manageability, and readiness for surgery. They valued the opportunity to make active choices when appropriate and appreciated having the right to delegate decisions to healthcare professionals. From a frail older adult’s perspective, team-based approaches in preoperative care, such as CGA and care, offer benefits in terms of involvement and satisfaction. However, the thorough evaluation of postoperative outcomes remains necessary. Trial registration OSF registry: https://osf.io/ch49n , registered on Sep 04, 2023.